Information actions in science and technology: institutionalities, agencies and subjects (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2016)
Considering the influence of new agency forms - intervention and interaction among subjects - in the context of information intermediation, we aim to approach information actions in Science and Technology (S&T) taking into consideration the institutionalities involved. For such, we assume there is an influence of a theoretical model emerging in Information Science (IS) regarding current inventive and interactive form propitiated by the Web. The text is structured in two central topics bringing: i) theoretical and epistemic constructions of the "information action" concept; and ii) a certain interpretation oriented by the "informational action in S&T" construct, taking as its object the actions performed by IBICT (Brazilian Institute for Information in Science and Technology), directed towards excellence in information. Finally, we discuss how limitations of the "systemic model" propitiate the construction of new study objects in the model emerging in IS from theoretical innovations and counterpoints thoughts facing the diverse forms of information action, considering, for instance, the action of subjects on what concerns the validation of information in the current scenery of institutional intermediation.Key words: Information actions; Information in science and technology; Information Science; Instituto Brasileiro de Informação em Ciência e Tecnologia Link: http://www.scielo.br/pdf/pci/v20n4/1413-9936-pci-20-04-00129.pdf